Prawne aspekty własności muzułmańskiej w prawie polskim - Kiliszkiewicz, Aleksander (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article addresses the issue of legal regulations on Muslim property in Poland. It contains information concerning a waqf and the principles of managing the assets of the Muslim Religious Union in Poland, with particular emphasis on the assets of the Union and the assets of the Muslim communities. The author analyses the legal situation on the basis of statutory regulations, as well as the bylaws of the Muslim Religious Union and the provisions of Sharia law. In addition, the article includes a brief historical background of Islam in Poland
Keywords: islam; muzułmanie; Muzułmański Związek Religijny w RP; Tatarzy; religia; wakuf; własność